2021
DOI: 10.1071/an21093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of faecal microbiota transplantation on the growth performance, intestinal microbiota, jejunum morphology and immune function of laying-type chicks

Abstract: Context Recent studies have indicated that the early stage of growth is a critical window for intestinal microbiota manipulation to optimise the immunity and body growth. Faecal microbiota transplantation (FMT) is often used to regulate intestinal microbiota colonisation. Aims The aim of this study was to explore the effect of FMT on the growth performance, intestinal microbiota, jejunum morphology and immune function of newly hatched laying-type chicks. Methods The chicks (Hy-line Brown) were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Fu et al showed phenotypic changes still present up to 16 weeks of age in laying hens after FMT administration during the first five weeks of life [ 49 ]. Yu et al showed persistency of a transplanted microbiota from an adult donor through three weeks of life when administrated to newly hatched laying hens on days 1, 3, and 5 [ 50 ]. Similarly, the microbiota transferred in the present study persisted for six weeks after being administered only once on day one of life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fu et al showed phenotypic changes still present up to 16 weeks of age in laying hens after FMT administration during the first five weeks of life [ 49 ]. Yu et al showed persistency of a transplanted microbiota from an adult donor through three weeks of life when administrated to newly hatched laying hens on days 1, 3, and 5 [ 50 ]. Similarly, the microbiota transferred in the present study persisted for six weeks after being administered only once on day one of life.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the microbial composition of the intestinal microbiota influences poultry performance [ 54 ], likely due to some bacterial species having the capacity to improve feed conversion, at least in part, by increasing the production of volatile fatty acids (VFA) [ 55 , 56 ]. Microbial transplantation in chickens has been attempted to promote growth performance, with inconsistent results [ 47 , 49 , 50 ]. The present study expected that colonization with a highly diverse microbiota containing lactic acid bacteria (i.e., Lactobacillu s spp.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study determined the growth performance and body composition of H. illucens-fed diets containing different strains. Adding microorganisms to feeds can promote animal growth and development [35][36][37]. Lee et al [38] reported that adding B. subtilis to feed improved growth performance and nutrient digestibility in weaned piglets.…”
Section: Discussionmentioning
confidence: 99%